2021
DOI: 10.3390/plants10112281
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptomic and Proteomic Exploration of Molecular Regulations in Quinoa Responses to Ethylene and Salt Stress

Abstract: Quinoa (Chenopodiumquinoa Willd.), originated from the Andean region of South America, shows more significant salt tolerance than other crops. To reveal how the plant hormone ethylene is involved in the quinoa responses to salt stress, 4-week-old quinoa seedlings of ‘NL-6′ treated with water, sodium chloride (NaCl), and NaCl with ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC) were collected and analyzed by transcriptional sequencing and tandem mass tag-based (TMT) quantitative proteomics. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Particularly those synthesized in the ornithine and raffinose pathways but also the accumulation of soluble sugars and proline, which also contribute to the cellular osmotic adjustment (reviewed by Bascunan-Godoy et al , (2016) and Hinojosa et al , (2018)). This enhanced accumulation of ROS detoxification enzymes has been recently described in 4-weeks old quinoa seedlings subjected to salinity stress (Ma et al , 2021). In line with this, numerous antioxidant enzymes overrepresented in seeds harvested from rainfed conditions were categorized into catabolic process BP-GO term, such as L-ascorbate peroxidases (AUR62044027-RA, AUR62003342-RA), peroxidase (POD) (AUR62024052-RA), cytochrome C peroxidase (AUR62003343-RA), peroxidase C1C (AUR62026666-RA), peroxidase 4 (AUR62012343-RA, AUR62009723-RA), chatepsin B (AUR62001249-RA), plastidial pyruvate kinase 2 (AUR62021072-RA), peroxiredoxin-2E (AUR62037884-RA), fructose-bisphosphate aldolases 3 (AUR62033531-RA, AUR62028580-RA), glutathione S-transferase (GST) (AUR62008599-RA) and Cu/Zn superoxide dismutase (SOD) (AUR62000929-RA).…”
Section: Go Terms Showed Differential Enrichment Of Antioxidant-relat...mentioning
confidence: 55%
“…Particularly those synthesized in the ornithine and raffinose pathways but also the accumulation of soluble sugars and proline, which also contribute to the cellular osmotic adjustment (reviewed by Bascunan-Godoy et al , (2016) and Hinojosa et al , (2018)). This enhanced accumulation of ROS detoxification enzymes has been recently described in 4-weeks old quinoa seedlings subjected to salinity stress (Ma et al , 2021). In line with this, numerous antioxidant enzymes overrepresented in seeds harvested from rainfed conditions were categorized into catabolic process BP-GO term, such as L-ascorbate peroxidases (AUR62044027-RA, AUR62003342-RA), peroxidase (POD) (AUR62024052-RA), cytochrome C peroxidase (AUR62003343-RA), peroxidase C1C (AUR62026666-RA), peroxidase 4 (AUR62012343-RA, AUR62009723-RA), chatepsin B (AUR62001249-RA), plastidial pyruvate kinase 2 (AUR62021072-RA), peroxiredoxin-2E (AUR62037884-RA), fructose-bisphosphate aldolases 3 (AUR62033531-RA, AUR62028580-RA), glutathione S-transferase (GST) (AUR62008599-RA) and Cu/Zn superoxide dismutase (SOD) (AUR62000929-RA).…”
Section: Go Terms Showed Differential Enrichment Of Antioxidant-relat...mentioning
confidence: 55%
“…However, recent experiments with Arabidopsis have documented that ACC acts as a signaling molecule and is able to control seedling growth independently of ethylene [254]. This finding was supported by a molecular analysis that correlated with ethylene and ACCmediated regulation of gene expression in quinoa under hyperosmotic salinity [255]. Based on the general observation that ACC deaminase producing bacteria attenuate adverse effects of long-term stress, such as salinization of soil, it was concluded that in these situations ACC production will exceed its degradation, and its concentration in plants will finally reach a level to inhibit the synthesis of essential metabolites [256].…”
Section: Ethylene and Accmentioning
confidence: 82%
“…A comprehensive review article on ethylene and salt stress tolerance was recently published, summarizing the findings up to 2021 [ 83 ], so only more recent publications are discussed here. A genome-wide transcriptome and proteome analysis in quinoa to examine its ethylene-regulated salt tolerance revealed involvement of three ERFs and promotion of ROS by ethylene-enhanced SOD activity [ 84 ]. Furthermore, the authors showed that a variety of transporters (including a high-affinity K + transporter, four nitrate and phosphate transporters, a cation/H + antiporter, a Na + /Ca 2+ exchanger, and an aquaporin) were involved.…”
Section: Ethylene and Jasmonates Action And Response Mechanism Under ...mentioning
confidence: 99%